«Evaluation of a traumatic combat experience» method for service members-combatants - Колесніченко, О. С. (Київський національний університет імені Тараса Шевченка, 2018)
The article presents the method «Evaluation of a traumatic combat experience» developed for assessment of service members of the National Guard of Ukraine. In contrast to the existing methods diagnosing a combat traumatic experience, the proposed psychological diagnostic tool expands the narrow framework of the «combat psychological trauma» concept and describes combat psychological traumatisation through the terminology of a social situation within which a service member’s personality is developed. This method combines the objective and subjective indicators of a danger at combat situations; it assesses a specific situation of participation in hostilities and the context in which it is unfolded; and it also assess factors contributing to or preventing personal traumatisation. The method consists of 39 statements and corresponding scales: the first one describes the adverse social conditions that are the result of social interactions in the zone of local conflict; the second one reveals specific characteristics of combat operations that are a source of traumatisation; the third scale assesses severity of life-threatening during army actions. Two more scale describes the resources available to a service member to overcome an unfavourable situation of participation in combat actions: the fourth one estimates resources to overcome the traumatic situation, which are based on readiness for participation in hostilities; the fifth one estimates resources existing due to belonging to a particular reference or social group. Each of the determined factors has its own weight in the formation of a combat psychic trauma. The method general indicator allows a psychologist to determine a degree of a service member’s psychological traumatisation due to his/her combat experience. It has been determined that normative values for the method scales for service members from other armed groups may differ considerably, since most of the National Guard’s personnel of the Ukrainian National Service recently serve on the second or third line of the united force operation.

У статті подано результати розробленої методики «Оцінки травматичності бойового досвіду» у військовослужбовців Національної гвардії України. На відміну від існуючих методик діагностики травматичності бойового досвіду, в розроблюваному психодіагностичному інструментарії здійснюється вихід за вузькі рамки поняття «бойова психічна травма» і описується процедура бойової психологічної травматизації через термінологію соціальної ситуації, в якій відбувається розвиток особистості військовослужбовця. Дана методика поєднує в собі об’єктивні та суб’єктивні показники небезпечності ситуацій бойових дій; оцінку конкретної ситуації участі в бойових діях та контексту, в якій вона розгортається; оцінку чинників, що сприяють та перешкоджають травматизації особистості. Вона складається з 39 тверджень і відповідних шкал: перша – описує несприятливі соціальні умови, які є наслідком особливостей соціальної взаємодії в зоні локального конфлікту; друга – наявні характеристики бойових дій, що стають джерелом травматизації; третя – реальність загрози життю під час участі в бойових діях. Ще дві шкали описують наявні у військовослужбовця ресурси для подолання несприятливості ситуації участі в бойових діях: четверта – ресурс подолання травматичності ситуації, який дає сформована готовність до участі в бойових діях; п’ята – ресурс, який дає приналежність до певної референтної та соціальної групи. Кожен із виділених чинників має власну вагу у формуванні бойової психічної травми. Загальний показник за методикою дозволяє визначити рівень психологічної травматичності бойового досвіду військовослужбовця. Визначено, що норми за шкалами методики для військовослужбовців інших збройних формувань можуть значно відрізнятися, бо більшість військовослужбовців НГУ останнім часом несуть службу на другій-третій лінії проведення операції об’єднаних сил.
Методика «Оцінки травматичності бойового досвіду» у військовослужбовців-учасників бойових дій
Keywords: combat actions; post-traumatic stress disorder; acute stress disorder; traumatic situation; service member; бойові дії; посттравматичний стресовий розлад; гострий стресовий розлад; травматична ситуація; військовослужбовці